PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL DAN UKURAN PERUSAHAAN TERHADAP KUALITAS LABA DENGAN MANAJEMEN LABA SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021 - Dian Nesti Lestari Hulu (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2023)
This study aims to determine the effect of managerial ownership, institutional ownership and company size on earnings management partially. To determine the effect of earnings management mediating the effect of managerial ownership, institutional ownership and company size on earnings quality partially. The total population in this study was 195 with a sample of 105 data observations. The analysis technique used is path analysis. The results show that managerial ownership has no significant effect on earnings quality, institutional ownership has a significant positive effect on earnings quality, firm size has a significant positive effect on earnings quality, earnings management has no effect on earnings quality, managerial ownership has no effect on earnings management, institutional ownership has not has an effect on earnings management, firm size has a significant positive effect on earnings management, earnings management does not mediate the relationship between managerial ownership on earnings quality, earnings management does not mediate the relationship between institutional ownership on earnings quality and earnings management does not mediate the relationship between firm size on earnings quality in Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2017-2021 Period.